A Legal Perspective on Employers’ Obligations to Promote Awareness of Menstrual Leave Rights in Indonesia - Margolang, Fahmi Ihsan; Sulastri, Dewi; Kurniawan, Wawan (Journal of Ecohumanism, 2025)
This study aims to analyze the obligations of companies in socializing menstrual leave right for female employees in Indonesia, both from a national legal aspect and an international perspective. The study uses a normative legal approach supported by empirical data through interviews with a number of female workers. The analysis was conducted on the main regulation such as Law No. 13 of 2003 concerning Manpower, PP No. 78 of 2018 concerning Wages, Law No. 36 of 2009 concerning Health, and Law N0. 40 of 2007 concerning Limited Liability Companies, and linked to international standards such as the CEDAW Convention. The results of the study show that although menstrual leave right have been regulated normatively, the obligation to socialize them ha snot been carried out evenly by companies. The lack of socialization causes many workers to be unaware these rights, which ultimately results in violations of the principles of justice and work protection. These findings are analyzed using the justice theory and the legal compliance theory, and are reinforced by good practices in certain companies. This study recommends the need for integration of socialization of menstrual leave right into CSR policies and company management systems as a form of substantive compliance with fair and inclusive labor laws.